Protein synthesis blockade prevents fear memory reactivation via inhibition of engram synapse strengthening - Ilgang Hong; Yeonjun Kim; Hyunsu Jung; Chang-Ho Kim; Jun-Hyeong Cho; Bong-Kiun Kaang (Proceedings of the National Academy of Sciences, 2026)
Memory relies on ensembles of engram cells in the brain. While previous studies have established the existence of these cells, the relationship between cellular and synaptic activity remains unclear. To address this, we applied the dual-enhanced green fluorescent protein reconstitution across synaptic partners (dual-eGRASP) technique in mice to examine synaptic connectivity between the ventral CA1 and the basal amygdala during memory formation. We found that contextual fear conditioning increased engram-to-engram synapse (engram synapse) density and induced structural potentiation, highlighting their importance in associative memory. Additionally, we investigated the role of protein synthesis in memory formation by drug-induced amnesia using anisomycin, a protein synthesis inhibitor. Mice injected with anisomycin once (1xANI) showed impaired natural recall but still displayed fear responses upon optogenetic reactivation. In contrast, mice that received four anisomycin injections over 6 h (4xANI) showed significantly impaired natural recall and failed to exhibit fear responses upon optogenetic reactivation. This behavioral phenotype correlated with synaptic changes as assessed using dual eGRASP, where 1xANI mice exhibited no significant reduction in engram synapse density but had significantly smaller spine sizes, whereas 4xANI mice showed both a significant reduction in engram synapse density and spine size. Our results indicate that protein synthesis inhibition significantly reduces engram synapse density and spine size, changes that correlate with reductions in fear memory during both natural and artificial recall.